Centromeres and kinetochores : discovering the molecular mechanisms underlying chromosome inheritance - Black, Ben E. (Springer, 2017)
This book presents the latest advances concerning the regulation of chromosome segregation during cell division by means of centromeres and kinetochores. The authors cover both state-of-the-art techniques and a range of species and model systems, shedding new light on the molecular mechanisms controlling the transmission of genetic material between cell divisions and from parent to offspring. The chapters cover five major areas related to the current study of centromeres and kinetochores: 1) their genetic and epigenetic features, 2) key breakthroughs at the molecular, proteomic, imaging and biochemical level, 3) the constitutive centromere proteins, 4) the role of centromere proteins in the physical process of chromosome segregation and its careful orchestration through elaborate regulation, and 5) intersections with reproductive biology, human health and disease, as well as chromosome evolution. The book offers an informative and provocative guide for newcomers as well as those already acquainted with the field.
Keywords: Centromere.; Chromosomes.; Proteins.; Cellular control mechanisms.; elektronické knihy; electronic books